The casque-headed tree-frog Corythomantis greeningi: clarifying some points on its biology - Jared, Carlos; Antoniazzi, Marta Maria (Zootaxa, 2008)
Among the anurans inhabiting the semi-arid areas of Brazil (Caatinga), the casque-headed tree-frog Corythomantis greeningi Boulenger 1896 is one of the most curious species. It is considered of wide occurrence in the Caatinga (Rodrigues, 2005) and is also found in some areas of the Cerrado, the Brazilian savannah (Colli et al, 2002). C. greeningi is characterized by its distinctive and flattened head, in which the helmet-shaped skull together with the head skin form a single coossified structure. This type of head has been associated with phragmosis (a term used for animals which close holes using parts of the body, in this particular case the head) (Jared et al., 2005). The species is well adapted to the xeric environment which led to the hypothesis that the peculiar head may function as a protection from desiccation when the animal hides inside holes. Nevertheless, even during periods of intense drought (in general in July and August) we observed these frogs remaining active. We thus inferred that the head should not be the main protection of the animal against desiccation.